2013
DOI: 10.3354/ab00507
|View full text |Cite
|
Sign up to set email alerts
|

Effects of indirect toxicity of interacting Cd–Zn in a planktonic marine system

Abstract: Traditional toxicity bioassays usually assess the effects of single substances on isolated species, which does not, however, allow the identification of potential effects in natural systems. In addition, quantitative estimations of metal uptake in top consumers due to feeding are generally focused on the individual level and do not evaluate the consequences of metal addition at demographic or population levels. An experimental system, composed of the marine microalga Nannochloris oculata Droop, 1955 and the he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Although our study was focused on arsenic, at concentrations currently occurring in some natural ponds (Pell et al 2013), most likely these animals are not exposed to a single heavy metal, which may influence in the rotifer response to these toxicants (Jara and Aránguiz-Acuña 2013). Ríos-Arana et al (2005) showed contrasting effects on induction of heat shock protein HSP60 by the rotifer Plationus patulus when was exposed to arsenic alone and to arsenic mixed with other heavy metals.…”
Section: Discussionmentioning
confidence: 99%
“…Although our study was focused on arsenic, at concentrations currently occurring in some natural ponds (Pell et al 2013), most likely these animals are not exposed to a single heavy metal, which may influence in the rotifer response to these toxicants (Jara and Aránguiz-Acuña 2013). Ríos-Arana et al (2005) showed contrasting effects on induction of heat shock protein HSP60 by the rotifer Plationus patulus when was exposed to arsenic alone and to arsenic mixed with other heavy metals.…”
Section: Discussionmentioning
confidence: 99%
“…Kippler et al (2012) found that early-life low-level cadmium exposure was associated with lower child intelligence scores. Interactions between Cd and other molecules and ions, such as PCB (Buha et al, 2013) or zink (Jara and Aránguiz-Acuña, 2013), may lead to enhanced Cd toxicity.…”
Section: Toxicity Mechanisms Cadmium Toxicitymentioning
confidence: 99%
“…These results suggest that zooplankton may be exposed to metals through interaction with metal contaminated particles and/or through dietary uptake of metal contaminated food. Recently, several laboratory investigations have shown that dietary uptake is one of the major sources of metal accumulation in zooplankton (Adam et al, 2002;Barata et al, 2002;Jara and Aránguiz-Acuña, 2013). Furthermore, high chlorophyll-a was observed throughout the year, specifically during PRM and MON.…”
Section: Discussionmentioning
confidence: 93%